Global Characteristics of Electromagnetic Ion Cyclotron Waves Deduced From Swarm Satellites. Issue 2 (24th February 2018) - Kim, Hyangpyo; Hwang, Junga; Park, Jaeheung; Bortnik, Jacob; Lee, Jaejin
Abstract: It is well known that electromagnetic ion cyclotron (EMIC) waves play an important role in controlling particle dynamics inside the Earth's magnetosphere, especially in the outer radiation belt. In order to understand the results of wave‐particle interactions due to EMIC waves, it is important to know how the waves are distributed and what features they have. In this paper, we present some statistical analyses on the spatial distribution of EMIC waves in the low Earth orbit by using Swarm satellites from December 2013 to June 2017 ( 3.5 years) as a function of magnetic local time, magnetic latitude, and magnetic longitude. We also study the wave characteristics such as ellipticity, wave normal angle, peak frequency, and wave power using our automatic wave detection algorithm based on the method of Bortnik et al. (2007, https://doi.org/10.1029/2006JA011900). We also investigate the geomagnetic control of the EMIC waves by comparing with geomagnetic activity represented by Kp and Dst indices. We find that EMIC waves are detected with a peak occurrence rate at midlatitude including subauroral region, dawn sector (3–7 magnetic local time), and linear polarization dominated with an oblique propagating direction to the background magnetic field. In addition, our result shows that the waves have some relation with geomagnetic activity; that is, they occur preferably during the geomagnetic storm's late recovery phase at low Earth orbit. Key Points: A statistical analysis of EMIC waves using Swarm satellites is performed EMIC waves are observed mainly at midlatitude including the subauroral region and dawn sector at low Earth orbit Approximately 50% of EMICs are related to geomagnetic storms and occur mainly during the storm recovery phase